Seismic Energy Analysis as Generated by Impact and Fragmentation of Single‐Block Experimental Rockfalls. Issue 6 (27th June 2018) - Saló, L.; Corominas, J.; Lantada, N.; Matas, G.; Prades, A.; Ruiz‐Carulla, R.
Abstract : The analysis of seismic signals obtained from near‐source triaxial accelerometer recordings of two sets of single‐block rockfall experiments is presented. The tests were carried out under controlled conditions in two quarries in northeastern Spain; in the first test (Foj limestone quarry, Barcelona), 30 blocks were released with masses ranging between 475 and 11, 480 kg. The second test (Ponderosa andesite quarry, Tarragona) consisted of the release of 44 blocks with masses from 466 to 13, 581 kg. An accelerometer and three high‐speed video cameras were deployed, so that the trajectories, velocities, and block fragmentation could be tracked precisely. These data were used to explore the relationship between seismic energy and rockfall kinetics (the latter obtained from video analysis). We determined absolute and relative values of seismic energy and used them to estimate rockfall volumes. Finally, the seismic signature of block fragmentation was assessed in both the frequency and time domains. The ratios of seismic energy after impact to kinetic energy before impact ranged between 10 −7 and 10 −4 . These variables were weakly correlated. The use of seismic energy relative to impacting kinetic energy was preferred for the estimation of volumes. Block fragmentation impacts were dominated by higher acceleration spectrum centroid frequencies than those of nonfragmentation impacts: 56.62 ± 2.88 and 48.46 ± 4.39 Hz at Foj and 52.84 ± 12.73 and 38.14 ± 4.73 Hz at Ponderosa. Plain Language Summary: Gravitational instability movements on mountain slopes are spontaneous in nature. In most cases, continuous seismic recordings are the only available data; thus, inference techniques are used to approximate the initial characteristics of the detached mass. Here we perform two sets of individual rock block release experiments in a highly monitored setting in northeastern Spain; in addition to the seismic instrumentation, a detailed study of block properties and the deployment of video cameras allow an accurate determination of the input parameters (volumes and impacting speeds), which are usually unknown in natural settings. This is used to relate seismic observations to known characteristics of the performed block releases. We find that (1) radiated elastic energies from the point of impact are significantly smaller than the impact energy, regardless of block breakage, (2) the usage of kinetic energy is preferred for the estimation of rockfall volumes, and (3) block fragmentation can be characterized by means of individual parameters associated with the radiated wave frequencies. These results should shed further light on how efficient the conversion of impact to radiated elastic energy is and on the level of inference that can be achieved based on seismic signals. Key Points: Seismic energy is 10 −7 to 10 −4 of impact kinetic energy Block volume is best estimated from impact kinetic energy The acceleration spectrum centroid frequency of breakage impacts is higher than that of intact blocks